Novel and recurrent BRCA1/BRCA2 germline mutations in patients with breast/ovarian cancer: a series from the south of Tunisia - Dorra Ben Ayed-Guerfali (Journal of Translational Medicine, 2021)
Abstract Background The incidence of breast cancer (BC) and/or ovarian cancer (OC) is increasing in Tunisia especially in young women and mostly those with family history. However, the spectrum of BRCA mutations remains little explored in Tunisian patients in particular in the southern region. Methods We sequenced the entire coding regions of BRCA1and BRCA2 genes using next generation sequencing (NGS) in 134 selected patients with BC and/or OC. Results Among the 134 patients, 19 (14.17%) carried pathogenic mutations (10 are BRCA1 mutation carriers and 9 are BRCA2 mutation carriers) that are mainly frameshift index (76.9%). Interestingly, 5 out of the 13 variants (38.46%) were found at least twice in unrelated patients, as the c.1310-1313 delAAGA in BRCA2 and the c.5030_5033 delCTAA that has been identified in 4/98 BC patients and in 3/15 OC patients from unrelated families with strong history of cancer. Besides recurrent mutations, 6 variant (4 in BRCA1 and 2 in BRCA2) were not reported previously. Furthermore, 3 unrelated patients carried the VUS c.9976A > T, (K3326*) in BRCA2 exon 27. BRCA carriers correlated significantly with tumor site (p = 0.029) and TNBC cases (p = 0.008). In the groups of patients aged between 31 and 40, and 41–50 years, BRCA1 mutations occurred more frequently in patients with OC than those with BC, and conversely BRCA2 carriers are mostly affected with BC (p = 0.001, and p = 0.044 respectively). Conclusions The overall frequency of the BRCA germline mutations was 14.17% in patients with high risk of breast/ovarian cancer. We identified recurrent mutations as the c.1310_1313 delAAGA in BRCA2 gene and the c.5030_5033 delCTAA in BRCA1 gene that were found in 4% and 20% of familial BC and OC respectively. Our data will contribute in the implementation of genetic counseling and testing for families with high-risk of BC and/or OC.